Marine Macro-Debris Pollution on the Coast of Negeri Haruku Village - Juliana Wilmiena Tuahatu; Gratia Dolores Manuputty; Marlin Chrisye Wattimena; Fahrul Rozy Fakaubun (Politeknik Negeri Sambas, 2026)
Marine debris is an environmental issue of both national and global concern, particularly marine macro-debris. This study was conducted to determine the level of marine macro-debris pollution along the coast of Negeri Haruku village. Data were collected at three sites considered representative of the Negeri Haruku coastline. A 100-m shoreline transect was used for data collection and divided into 20 segments, from which five segments were randomly selected for sampling. The Clean Coast Index (CCI) was calculated to assess beach cleanliness, while the Plastic Abundance Index (PAI) was used to measure the proportion of plastic debris relative to the total amount of beach debris. The results showed that plastic debris dominated other debris types at all observation sites. This was reflected in the PAI values, namely 4.82 at the site near the river mouth, indicating high plastic density; 1.51 at Hii Beach, indicating moderate plastic density; and 6.09 at Totu Beach, indicating high plastic density. Totu Beach had the highest CCI value of 22.2, indicating a very dirty condition, while the site near the river mouth had a CCI value of 12.6, indicating a dirty condition. In contrast, Hii Beach was classified as clean, with a CCI value of 3.82. A paradoxical pattern was also observed in this study: even at a site with no apparent human activity, debris density was higher (5.55 ± 0.77 items/m²) than at the other two sites. This suggests that the debris may have originated from other locations and been transported by ocean currents. Based on the Clean Coast Index, only Hii Beach was classified as clean, whereas the site near the river mouth and Totu Beach were classified as dirty.